2019
DOI: 10.3390/app9081636
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Silver Nanoparticle Arrays by Hot Embossing and Sputter Deposition for Surface-Enhanced Raman Scattering

Abstract: Surface-enhanced Raman scattering (SERS) spectroscopy has attracted a lot of attention over the past 30 years. Due to its extreme sensitivity and label-free detection capability, it has shown great potential in areas such as analytical chemistry, biochemistry, and environmental science. However, the major challenge is to manufacture large-scale highly SERS active substrates with high controllability, good reproducibility, and low cost. In this study, we report a novel method to fabricate uniform silver nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…On pure ZnO and Ag/ZnO MSs (5 min and 1.9 mM) Raman signal associated to R6G is not identified, due to Ag absence and lower Ag content, respectively. However, for the other samples, clearly defined peaks can be seen at 154, 235, 308 374, 533, 607, 613, 774, 1123, 1182, 1312, 1358, 1508, and 1571 cm −1 , which are associated to R6G according to other reports [21][22][23][24]. Moreover, it is evident that the SERS activity of the Ag/ZnO substrates improves by increasing the UV irradiation time.…”
Section: Detection Of R6g With Sers Substratessupporting
confidence: 70%
“…On pure ZnO and Ag/ZnO MSs (5 min and 1.9 mM) Raman signal associated to R6G is not identified, due to Ag absence and lower Ag content, respectively. However, for the other samples, clearly defined peaks can be seen at 154, 235, 308 374, 533, 607, 613, 774, 1123, 1182, 1312, 1358, 1508, and 1571 cm −1 , which are associated to R6G according to other reports [21][22][23][24]. Moreover, it is evident that the SERS activity of the Ag/ZnO substrates improves by increasing the UV irradiation time.…”
Section: Detection Of R6g With Sers Substratessupporting
confidence: 70%
“…For the uniform nanostructured Working Electrode, our research team has previously developed a SERS active substrate manufacturing technology [ 24 ], which produces a nanostructured PC substrate decorated with uniformly distributed and closely packed noble metal nanospheres. The SERS active substrate showed good uniformity and can be easily reproduced.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the development of electrodes to monitor the prognosis of blood cancer patients is still rare [12,26,27]. The use of Ag nanostructures with AAO templates is a simple and inexpensive method to obtain a blood cancer prognosis monitoring sensor [28,29]. This study found that Ag nanosquare arrays and Ag thin films with different biological material media possess different optical and electrochemical characteristics.…”
Section: Introductionmentioning
confidence: 94%